Game of thrones: book one of a song of ice and fire - Martin, George R. R. (Harper Voyager London, 2011)
Martin unfolds with astonishing skill a tale of truly epic dimensions, thronged with memorable characters, a story of treachery and ambition, love and magic. Set in a fabulous world scarred by battle and catastrophe over 8000 years of recorded history, it tells of the deeds of men and women locked in the deadliest of conflicts and the terrible legacy they will leave their children. (http://www.harpercollins.co.nz)
Keywords: Fantasy fiction